Excitotoxic activation of the NMDA receptor results in inhibition of calcium/calmodulin kinase II activity in cultured hippocampal neurons - SB Churn; David D. Limbrick; Sompong Sombati; RJ DeLorenzo (1995)
Neurotoxic effects of excitatory amino acids have been implicated in various neurological disorders, and have been utilized for excitotoxic models of delayed neuronal cell death. The excitotoxic glutamate-induced, delayed neuronal cell death also results in inhibition of calcium/calmodulin-dependent kinase II (CaM kinase II). In this report, we characterized the glutamate-induced inhibition of CaM kinase II in relation to loss of intracellular calcium regulation and delayed neuronal cell death. Glutamate (500 microM for 10 min), but not KCl (50 mM), exposure resulted in a significant inhibition of CaM kinase II activity. The inhibition of CaM kinase II activity was observed immediately following excitotoxic glutamate exposure and present at every time point measured. Glutamate-induced inhibition of kinase activity and delayed neuronal cell death was dependent upon both the activation of the NMDA glutamate receptor subtype and the presence of extracellular calcium. The relationship between inhibition of CaM kinase II activity and loss of intracellular calcium regulation was also examined. Experimental conditions which resulted in significant neuronal cell death and inhibition of CaM kinase II activity also resulted in a long-term loss of intracellular calcium regulation. Thus, inhibition of CaM kinase II activity occurred under experimental conditions which resulted in loss of neuronal viability and loss of neuronal calcium regulation. Since the glutamate-induced inhibition of CaM kinase II activity preceded neuronal cell death, the data support the hypothesis that inhibition of CaM kinase II activity may play a significant role in excitotoxicity-dependent, delayed neuronal cell death.